The valley of horses : a novel - Auel, Jean M. (New York : Bantam Books, 2002)
Declared dead by the new leader of the ancient clan that has raised her, Ayla sets out to search for other humans like herself in prehistoric Europe.
Sequel to: The clan of the cave bear.
New York Times.
Voice of Youth Advocates (V.O.Y.A.).
Wilson's Fiction.
Young Adult.
Young Adult
Keywords: Ayla (Fictitious character) -- Fiction; Cro-Magnons -- Fiction; Glacial epoch -- Europe -- Fiction; Prehistoric peoples -- Europe -- Fiction; Ayla (Fictional character) -- Fiction; Cro-Magnons -- Fiction; Epic literature; Historical fiction; Ice age -- Fiction; Prehistoric peoples -- Europe -- Fiction